An Interpretation of Q.S. Al-Waqi’ah (56) Verse 79: The Perspective of Ma’na-Cum-Maghza - Ningrum, Anggun Puspita; Alamsah, Johan; Hendro, Beko; Aulia, Siti Rahma (Taqaddumi: Journal of Quran and Hadith Studies, 2025)
Cases of intolerance of certain groups have recently increased, particularly in the glorifying of the Qur'anic mushaf. These cases result from differing interpretations of the Qur'an. This study focuses on Surah Al-Waqi'ah: 79, which discusses touching the Qur'an in a state of purity. The community has numerous perspectives on the meaning of pure in the verse, resulting in an ongoing debate. This study employed a qualitative method, with the ma’na cum maghza hermeneutic approach serving as the analytical tool. The ma'na-cum-maghza is an interpretation approach that uses the original literal meaning (historical or explicit meaning) as the foundation for understanding the text's main message (implied meaning). The ma’na cum maghza approach begins with the meaning (ma'na) of a Quranic text as understood by the first audience and progresses to significance (maghza) for contemporary situations. According to the findings of this study, the meaning of al-muthahharun is more than just a human being free of hadas (impurities). Therefore, touching the Qur'an does not always require prior ablution.